Comparative Analysis of Financial Performance in Fiscal Decentralization Era Among Natural and Non-Natural Resources Region - Haryanto, Joko Tri (Research and Development Agency Ministry of Home Affairs, 2017)
Indonesia has a long history of fiscal decentralization. In terms of accountability and transparency, it is necessary to have performance appraisal of local financial indicators. This research was conducted by taking samples of natural and non-natural resources regions from the 2010 - 2014 period. From the result of the degree of decentralization indicator, the natural resources region has a low degree. In contrast, on non-natural resources regions, they have a higher degree and included in both good and very good criteria. Based on the independence local indicators, only Siak Regency has the greatest independence, while other natural resource regions have very small category and the instructional relationships pattern. In non-natural resources regions categories, all samples are independent enough and already independent with participatory and discretionary relationship pattern. In the harmonization among routine and developmental spending indicators, in natural resources regions, routine spending is relatively small. While in non- natural resources regions, routine spending allocation is also very dominant. From that result, the government should formulate an innovative non-public development pattern to further enhancing the participation of other stakeholders and also provide advocacy to Local Government to start limiting the routine personnel expenditure and prioritizing to infrastructure development that impacts the investment.